Risk Management Analysis of Tofu Production (Case Study of Ainul Tofu Business in Taliabu Island Regency) - Halim, Herlin; Rianda, La; Indarsih, Yusna (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2024)
This research aims to identify the risks of tofu production in the Tofu Ainul business, find out the prioritized risks, and determine the priority of alternative risk mitigation strategies for tofu production in the Tofu Ainul business in Taliabu Island Regency using the Failure Mode and Effect Analysis (FMEA) method to determine the highest risks and the Analytical Hierarchy Process (AHP) method to determine alternative risk mitigation strategies. The results of this research show that there are 16 types of risks, with the highest RPN in the raw material variable, namely the risk of fluctuating soybean raw material prices with an RPN of 194.7; in the production process variable, the risk of dust and foreign object contamination with an RPN of 56.6; and in the finished product variable, the risk of late delivery of tofu with an RPN of 120.0. The results of calculating alternative risk mitigation strategies for tofu production at the Ainul Tofu Business using the AHP method obtained 3 alternative strategy recommendations for reducing risks in tofu production. The alternative mitigation strategies are establishing cooperation (contact arrangement) with soybean farmer groups for the raw material variable with a weight of 0.470, improving sanitation in the tofu processing production area for the risk of the production process variable with the highest weight of 0.372, and choosing a reliable and timely delivery service for the risk of the finished product variable with the highest weight of 0.547.